A Simulink model for modified fountain codes - Nadhir Ibrahim Abdulkhaleq; Nahla Abdul Jalil Salih; Rajaa Salih Mohammed Hasan; Ihsan Jabbar Hasan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This paper introduces a Simulink model design for a modified fountain code. The code is a new version of the traditional Luby transform (LT) codes. The design constructs the blocks required for generation of the generator matrix of a limited-degree-hopping-segment Luby transform (LDHS-LT) codes. This code is especially designed for short length data files which have assigned a great interest for wireless sensor networks. It generates the degrees in a predetermined sequence but random generation and partitioned the data file in segments. The data packets selection has been made serialy according to the integer generated from both degree and segment generators. The code is tested using Monte Carlo simulation approach with the conventional code generation using robust soliton distribution (RSD) for degree generation, and the simulation results approve better performance with all testing parameter.